Re-Islamisation: the conversion of subculture from Abangan into Santri in Surakarta - Haedar Nashir; Mutohharun Jinan (Indonesian Journal of Islam and Muslim Societies, 2018)
This paper discusses the on-going process of re-Islamisation in Java. In the context of re-Islamisation process, a Muslim is expected to be a pious one, both from the aspect of belief, knowledge, and practice. The process is characterized by the intensification of Islamic ritual practice and the enforcement of Islamic norms in various aspects of life. Additionally, it is accompanied by the deterioration of animism—as represented by amulets, heirlooms and shamanism—which are popular among abangan communities. Amulet is a peculiar feature in the belief and life system of Javanese society, namely the belief in the magical objects used by the owner to gain power, convenience, and magnificence. In Surakarta, the phenomenon of the decline of ‘magical’ amulets is perceived as the conversion process from abangan to santri. Yet it is a dissimilar kind of conversion compared to the previous ones.It reaffirms that in Java, Islamisation is an unending process nuanced by the volatility of socio-political and cultural dynamics. Artikel ini membahas proses reislamisasi di masyarakat Jawa yang saat ini masihterus berlangsung. Reislamisasiadalah proses dimana seorang muslim menjadilebih islami, baik dari aspek keyakinan, pengetahuan, maupun pengamalanajaran agama. Reislamisasi ditandai denganmenguatnya pengamalan ritualIslam dan ditegakkannya norma-norma Islam dalam berbagai aspek kehidupan.Dalam waktu yang samadiiukutimelemahnya kepercayaan animistik, sepertikepercayaan pada jimat, pusaka dan perdukunan di kalangan masyarakatabangan. Jimat merupakan salah satu ciri penting dalam sistem kepercayaandan kehidupan masyarakat Jawa, yakni kepercayaan kepada benda-bendayang dikeramatkan yang digunakan pemiliknya untuk memperoleh kekuatan,kenyamanan, kemuliaan hidup. Di Surakarta terdapat fenomena komunitasabanganmeninggalkan jimat sebagai bagian dari proses konversi dari abanganmenuju ke santri.Ini merupakan konversi baru yang berbeda dengan konversilama. Hal ini menunjukkan bahwa proses islamisasi di Jawa sebagai prosesyang terus berlangsung mengikuti dinamika sosio-politik dan kultural yangberkembang di Jawa.